Morphometric, Meristic, and Growth Patterns of Hampala macrolepidota from the Kampar Kiri River, Mentulik Village, Kampar Regency, Riau Province - Siregar, Fuja Arsita; Efizon, Deni; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Hampala macrolepidotafishis a freshwater fish that inhabit the Kampar Kiri River.To understand themorphometrical, meristical characteristics and growth pattern of this fish, a research had been conducted from February-April 2018. There were 52 fishes (102-330 mm SL and 30.92-990 g BW) were captured from the river. There were 26 morphological characteristics measured and 11 meristical characteristics counted. Meristical characteristics of the fins were as follows: D. I, 11; P, 16; V, 9; A,7; C, 20, while the number of scale in the frontal area of the dorsal fin was 10-12, around the body was 22, around the base of the tail was 7-8 and in the lateral line was 27-28. There were 4 morphometrical characteristic differences between male and female, namely the distance between mouth and the base of pectoral fin, eye diameter, dorsal fin height and the base of caudal fin height. The length-weight relationship of the fish was allometric positive, 3.41 in female and 3.53 in male. Keywords:Freshwater fish, morphometrical characteristic, meristical characteristic, allometric positive